Establishing Monoxenic Culture of Arbuscular Mycorrhizal Fungus Glomus sp. Through In Vitro Root Organ Culture and Swietenia macrophylla King In Vitro Cultures - Romero-Ceciliano Marysol; Andrade-Torres Antonio; Artavia-Salazar Evelyn; Solís-Ramos Laura Yesenia (Agriculture)
In vitro cultivation of arbuscular mycorrhizal fungi (AMF) is challenging due to their biotrophic symbiosis. The principal aim of this study was to demonstrate the effect of establishing in vitro dual cultures of arbuscular mycorrhizal fungi (AMF) inoculated on Swietenia macrophylla (mahogany) roots on plant growth. Furthermore, it was sought to demonstrate that plant colonization by Glomeromycota can be achieved with a replicable protocol. This study established monoxenic cultures of carrot (Daucus carota) Ri T-DNA ROC inoculated with Glomus sp. on two-compartment plates. At 75 days, hyphal growth reached 223.93 mm in the root compartment and 103.71 mm in the hyphal compartment. Spores produced in vitro measured 26.14 ± 1.70 µm, smaller than ex vitro spores (101.2 ± 4.22 µm). Rhodotorula mucilaginosa was isolated from cultures and appeared to stimulate hyphal growth and root–fungal contact. From these cultures, a dual culture of mahogany inoculated with Glomus sp. was established. No significant differences were observed between inoculated and non-inoculated plants in stem length, root length, root number, or leaf number at 30 days. Spore production ranged from 10,166 to 27,696 per plate, averaging 14,795 ± 3301, with hyphal lengths of 3655.46 ± 308.75 mm. Hyphal development included running and branching patterns, with solitary and clustered spores. Spore diameter averaged 27.68 ± 3.85 µm. Arbuscular colonization reached 41.49% at 30 days and 52.13% at 75 days, exceeding rates reported for other culture systems. Monoxenic cultures are a reliable, aseptic source of high-quality inoculum, supporting biofertilizer production and biotechnological applications. These methods provide valuable tools for studies involving AMF, such as those demonstrated with mahogany.